Transformational Leadership and Its Impact on Employee Performance and Job Satisfaction - Susilawati Susilawati; Aglis Andhita Hatmawan; Mulyadi Mulyadi; Supriyadi Supriyadi; Anggalia Wisbasuri; Tomi Apra Santosa (Citra Media Publishing, 2026)
Transformational leadership has become increasingly important in contemporary organizations as rapid technological change, competitive pressures, and evolving employee expectations require leaders to foster motivation, adaptability, and sustainable performance. Despite extensive research on leadership effectiveness, the extent to which transformational leadership simultaneously contributes to employee performance and job satisfaction remains an important area of organizational and human resource management research. This study aims to examine the impact of transformational leadership on employee performance and job satisfaction and to explain how transformational leadership behaviors contribute to positive employee outcomes. The study employs a quantitative explanatory research design using a survey approach. Data are collected from employees through a structured questionnaire measuring transformational leadership, employee performance, and job satisfaction. Transformational leadership is assessed through the dimensions of idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The collected data are analyzed using descriptive statistics, reliability and validity testing, correlation analysis, and structural equation modeling to examine the hypothesized relationships among the constructs. The findings indicate that transformational leadership has a positive and significant effect on employee performance, suggesting that leaders who articulate an inspiring vision, encourage innovative thinking, provide individualized support, and demonstrate exemplary behavior can enhance employees’ effectiveness and work contributions. Transformational leadership also has a positive and significant effect on job satisfaction by strengthening employees’ motivation, recognition, psychological involvement, and positive perceptions of the work environment. Overall, the findings demonstrate that transformational leadership constitutes an important organizational resource for simultaneously improving employee performance and job satisfaction. The study provides theoretical implications for transformational leadership and organizational behavior literature and practical implications for organizations seeking to develop leadership practices that promote productive, satisfied, and highly engaged employees.